Techno-economic and environmental analyses to identify preferred sugarcane biorefinery scenarios to produce acrylic acid, propylene glycol and associated chemicals in a multiproduct platform approach - Brobbey, Mensah Sarpong (Stellenbosch : Stellenbosch University, 2025)
Brobbey, M. S. 2025. Techno-economic and environmental analyses to identify preferred sugarcane biorefinery scenarios to produce acrylic acid, propylene glycol and associated chemicals in a multiproduct platform approach. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/ef17bfaa-d4ea-4fd3-b8d6-33f899e64633